If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 = 5x + 7 Reorder the terms: 6 + 6x = 5x + 7 Reorder the terms: 6 + 6x = 7 + 5x Solving 6 + 6x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 6x + -5x = 7 + 5x + -5x Combine like terms: 6x + -5x = 1x 6 + 1x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + 1x = 7 + 0 6 + 1x = 7 Add '-6' to each side of the equation. 6 + -6 + 1x = 7 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 7 + -6 1x = 7 + -6 Combine like terms: 7 + -6 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| -3p+7=5-(12p+6) | | 2x+9=4x-9 | | -9x-36+7x=28 | | 8x-9=5x | | 7+2y-4=5y+12-2y | | -2x+8=30 | | -15x+22x-81=157 | | 4y-9y=30 | | 4x+5=-4+5x | | 5t+9t=98 | | X+5=4x-19 | | -245+18x-27x=196 | | 16m=13 | | -3(7p+3)-2(1-17p)=3(3+4p) | | 6x+3x-307=269 | | 5-6(2+y)=y-14 | | 5x-(4x+4)=3 | | 10=8(3y-4)-23y+20 | | 6x+2+4x+5=9x+3 | | x-121=0 | | -435-23x+7x=173 | | 4p-19=28 | | 7p+9=14+6p | | 4D=3D-8 | | -155+2x+6x=261 | | 2x+8=480 | | 12+4v=8 | | 5x-2=57 | | 94=-2(1+6p) | | 14k+55=11k+94 | | 9x+22=7x+16 | | 4x^2-36y^2=0 |